Students’ digital literacy analysis in Institut Pendidikan Tapanuli Selatan based on length of study and gender - Asriani Hasibuan; Derliana Hasibuan (Concept : Community Concern for English Pedagogy and Teaching, 2022)
The aim of this research is to analyze the digital literacy abilities of students at the South Tapanuli Institute of Education in terms of the length of study and gender. This research is quantitative and descriptive. Based on the research results, it can be concluded that students with different lengths of study and gender have different abilities to use technology. The achievement percentage for functional skills and beyond is 85% and 87% respectively, with males achieving 75% and females achieving 78%. The ability to find and select information is in the "very good" category with an achievement percentage of 85% and 87%. For critical thinking and evaluation, students in semester 5 achieved 65%, while students in semester 7 achieved 72%. Males achieved 75% and females achieved 78%. For cultural and social understanding, students in semester 5 achieved 50%, while students in semester 7 achieved 50%. Males achieved 53% and females achieved 40%. For e-safety, students in semester 5 achieved 70%, while students in semester 7 achieved 73%. Males achieved 70% and females achieved 72%. The results of the study also show that the comparison of digital literacy abilities of students with different lengths of study, semester 7 is greater than semester 5. The value of digital literacy for females is 87% higher than the value for digital literacy for males, which is 85%. Keywords: literacy digital; students; length of study; gender